Evidence of temperature and precipitation change over the past 100 years in a high-resolution pollen record from the boreal forest of Central European Russia. (May 2017) - Olchev, Alexander; Novenko, Elena; Popov, Viktor; Pampura, Tatiana; Meili, Markus
Near-annual pollen records for the last 100 years were obtained from a 65-cm peat monolith from a raised peat bog in the Central Forest State Natural Biosphere Reserve (southern part of the Valdai Hills, European Russia) and compared with the available long-term meteorological observations. An age–depth model for the peat monolith was constructed by 210 Pb and 137 Cs dating. Cross-correlation and the Granger causality analysis indicated a broad range of statistically significant correlations between the pollen accumulation rate (PAR) of the main forest-forming trees and shrubs ( Picea, Pinus, Betula, Tilia, Quercus, Ulmus, Alnus, and Corylus ) and the air temperature and precipitation during the previous 3 years. Results showed that high air temperatures during the growing season (May–September) in the year prior to the flowering led to an increase in pollen productivity of the main tree species. The statistically significant correlation between the PAR of trees and shrubs and winter precipitation of the current and previous years could reflect the influence of winter precipitation on soil water availability and as a result on tree growth and functioning in the spring.